(3eWGQM GdCfXGQs - (3GdcdfJQj, GdfhQj, CHh GdbGSe Hf eMeO Ydj Hf gGOj, J (B1292 (3g`s ((3eYjf GdOjf CMeO Hf QLH Ydjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3hHYO agPg ebJWaGJ ef eWGQM TjNfG (B... (3cJGH(B... (3hajg ebOeI hebGUO(B...s
(3BNQgG (B:s
(3hef Pdc jchf EfcGQ VQhQj ef GdOjf hJcPjHg caQG eY GdYde HCfg VQhQj hcPG jdRe GdGYJQGas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B184s
(3GdCYdGe(B: (3L(B1(3, U(B184s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis